2017
DOI: 10.3324/haematol.2016.161711
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and diagnostic relevance of NOTCH2 -and KLF2 -mutations in splenic marginal zone lymphoma

Abstract: Splenic marginal zone lymphoma (SMZL) is a small Bcell lymphoma distinguished by frequent 7q loss and the biased use of IGHV01-02. Massive sequencing techniques have demonstrated NOTCH2 and KLF2 gene mutations to be the most frequent mutations in SMZL, with NOTCH2 mutations occurring in 10-25% of SMZL cases, 1-3 and transcription factor KLF2 mutations present in 12-44% of SMZLs.1,4,5 The clinical impact of NOTCH2 alterations is controversial, with different studies reaching very distinct conclusions.3 Herein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Six discovery genome wide studies 16 implemented WGS or WES with an unbiased approach and subsequently confirmed the variants using targeted sequencing. The nine extension/confirmation studies 1,2,4,610,12 were hypothesis based, targeting pathways identified in discovery cohorts or validation of recurrently mutated genes. Three comparison studies 11,13,14 sequenced SMZL cases as reference points to compare other B-cell lymphomas.…”
Section: Resultsmentioning
confidence: 99%
“…Six discovery genome wide studies 16 implemented WGS or WES with an unbiased approach and subsequently confirmed the variants using targeted sequencing. The nine extension/confirmation studies 1,2,4,610,12 were hypothesis based, targeting pathways identified in discovery cohorts or validation of recurrently mutated genes. Three comparison studies 11,13,14 sequenced SMZL cases as reference points to compare other B-cell lymphomas.…”
Section: Resultsmentioning
confidence: 99%
“…KLF2 drives follicular B cell maturation in mice and its deletion results in an expansion of MZB cells. The role of KLF2 in human B cell development is not known; however, loss-of-function KLF2 mutations along with NOTCH2 mutations that increase the stability of the notch intracellular domain are the most commonly encountered mutations in human MZB cell lymphoma ( Campos-Martín et al, 2017 ). This implicates KLF2 in human B cell fate decisions, suggests a role for IFN-γ in B cell development, and supports its proposed involvement of the imbalance of B cell subsets in LN.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] FATHMM-XF analysis predicted the single nucleotide mutations detected in NCOA4, PTEN, and EPHA3 to be pathogenic (Table 2 ). NOTCH2 is one of the most frequently (10% to 25%) mutated genes in SMZL, [ 12 ] whereas NOTCH2 mutations are not found in chronic lymphocytic leukemia (CLL), mantle cell lymphoma (MCL), low grade follicular lymphoma (FL), or hairy cell leukemia (HCL). [ 13 , 14 ] The frameshift/deletion mutation we found in this case affects the C-terminal PEST domain of NOTCH2, which is critical for NOTCH2 proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%